2010
DOI: 10.1109/tasl.2009.2023170
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Robust Music Identification With Weighted Finite-State Transducers

Abstract: Abstract-We present an approach to music identification based on weighted finite-state transducers and Gaussian mixture models, inspired by techniques used in large-vocabulary speech recognition. Our modeling approach is based on learning a set of elementary music sounds in a fully unsupervised manner. While the space of possible music sound sequences is very large, our method enables the construction of a compact and efficient representation for the song collection using finite-state transducers.This paper gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…Accuracy for multi-conditional training Front-end. We test the modifications we propose in Section 2.1 to our baseline speech recognition front-end (similar to that reported in [1]) by training an acoustic model on CLEAN, building the FST from the songs in INDEX, and testing the modifications on the four sets of snippets. As shown in Table 2 adapting the front-end to the task of music recognition consistently improved identification accuracy across the different test sets.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Accuracy for multi-conditional training Front-end. We test the modifications we propose in Section 2.1 to our baseline speech recognition front-end (similar to that reported in [1]) by training an acoustic model on CLEAN, building the FST from the songs in INDEX, and testing the modifications on the four sets of snippets. As shown in Table 2 adapting the front-end to the task of music recognition consistently improved identification accuracy across the different test sets.…”
Section: Resultsmentioning
confidence: 99%
“…The above system achieved 99.9% identification accuracy over test snippets cut from clean recordings, and in [6,1] we showed that the system was robust to synthetic distortions. Nevertheless, we observed a significant degradation in accuracy when the test recordings were recorded with mobile phones.…”
Section: Modelingmentioning
confidence: 91%
See 3 more Smart Citations